2023
DOI: 10.1111/nicc.12880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of rehabilitation and ICU diary on critically ill patients: A systematic review and meta‐analysis

Abstract: Background: Various physical and mental sequelae reduce the quality of life (QOL) of intensive care unit (ICU) patients. Current guidelines recommend multi-angular approaches to prevent these sequelae. Some studies have demonstrated the clinical effectiveness of rehabilitation or the ICU diary against these sequelae, whereas others have not. Aim:The aims of the present study were to establish whether rehabilitation or the ICU diary was useful for reducing the severity of anxiety, depression, and posttraumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…A systematic review explored the impact of post-ICU rehabilitation and patient diaries on health-related quality of life, anxiety, depression and post-traumatic stress disorder (PTSD). 15 The meta-analysis demonstrated that rehabilitation initiated after ICU discharge improved health-related quality of life but did not impact anxiety, depression, or PTSD. Finally, a qualitative service evaluation of implementing games-based therapy (GBT) in an adult critical care Please note that the views expressed in this critical commentary are those of the authors and may not necessarily reflect the opinion of the Nursing in Critical Care editorial board, the British Association of Critical Care Nurses or Wiley.…”
Section: Two Further Interventions Are Explored In This Special Issuementioning
confidence: 98%
See 1 more Smart Citation
“…A systematic review explored the impact of post-ICU rehabilitation and patient diaries on health-related quality of life, anxiety, depression and post-traumatic stress disorder (PTSD). 15 The meta-analysis demonstrated that rehabilitation initiated after ICU discharge improved health-related quality of life but did not impact anxiety, depression, or PTSD. Finally, a qualitative service evaluation of implementing games-based therapy (GBT) in an adult critical care Please note that the views expressed in this critical commentary are those of the authors and may not necessarily reflect the opinion of the Nursing in Critical Care editorial board, the British Association of Critical Care Nurses or Wiley.…”
Section: Two Further Interventions Are Explored In This Special Issuementioning
confidence: 98%
“…Two further interventions are explored in this special issue. A systematic review explored the impact of post‐ICU rehabilitation and patient diaries on health‐related quality of life, anxiety, depression and post‐traumatic stress disorder (PTSD) 15 . The meta‐analysis demonstrated that rehabilitation initiated after ICU discharge improved health‐related quality of life but did not impact anxiety, depression, or PTSD.…”
mentioning
confidence: 99%
“…Recently, FGH has been added to prevent PICS, where F indicates family involvement, follow-up referrals, and functional reconciliation; G indicates good handoff communication; and H indicates handout material on PICS and PICS-family [ 3 , 5 ]. This bundle has beneficial effects that reduce deep sedation, immobilization, and anxiety [ 6 , 7 ]. This review focuses on rehabilitation in the ICU, including early mobilization, as a strategy for preventing and treating PICS.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that for many patients, rehabilitation continues beyond the walls of critical care (and the acute hospital) due to the profound impairments of critical illness 20 . To support the holistic nature of rehabilitation, adjuncts such as the use of patient diaries have been shown to ameliorate anxiety 21 . For musculoskeletal rehabilitation post‐ICU, studies have failed to address this due to the nature of single interventions 8 …”
mentioning
confidence: 99%
“…20 To support the holistic nature of rehabilitation, adjuncts such as the use of patient diaries have been shown to ameliorate anxiety. 21 For musculoskeletal rehabilitation Please note that the views expressed in this critical commentary are those of the authors and may not necessarily reflect the opinion of the Nursing in Critical Care editorial board, the British Association of Critical Care Nurses or Wiley. post-ICU, studies have failed to address this due to the nature of single interventions.…”
mentioning
confidence: 99%